Extraordinary dreams and how to work with them - Krippner, Stanley, 1932- (SUNY series in dream studies., 2002)
"From visions of a past life to glimpses of the future, history is full of accounts of unusual dreams. This fascinating book explores historical, scientific, and cross-cultural research on these sorts of extraordinary dreams, and offers practical suggestions on how to work with them - either individually or as a member of a dream group - to enhance one's intellectual, emotional. and spiritual health. Each chapter is devoted to a particular type of dream, and presents a summary of research data on their nature. Specific categories of dreams discussed include creative, lucid, out-of-body, pregnancy, healing, collective, telepathic, clairvoyant, precognitive, past-life, initiation, and spiritual visitation dreams, as well as dreams within dreams. Entertaining and instructive, this book points the way to an expanded conception of human potential for the twenty first century."--Jacket